NTRK3 exhibits a pro‐oncogenic function in upper tract urothelial carcinomas - Lee‐Moay Lim; Yi‐Chen Lee; Ting‐Wei Lin; Zi‐Xuan Hong; Wei‐Chi Hsu; Hung‐Lung Ke; Daw‐Yang Hwang; Wen‐Yu Chung; Wei‐Ming Li; Hui‐Hui Lin; Hung‐Tien Kuo; A‐Mei Huang (Kaohsiung Journal of Medical Sciences, 2024)
Abstract Neurotrophic receptor tyrosine kinase 3 (NTRK3) has pleiotropic functions: it acts not only as an oncogene in breast and gastric cancers but also as a dependence receptor in tumor suppressor genes in colon cancer and neuroblastomas. However, the role of NTRK3 in upper tract urothelial carcinoma (UTUC) is not well documented. This study investigated the association between NTRK3 expression and outcomes in UTUC patients and validated the results in tests on UTUC cell lines. A total of 118 UTUC cancer tissue samples were examined to evaluate the expression of NTRK3. Survival curves were generated using Kaplan–Meier estimates, and Cox regression models were used for investigating survival outcomes. Higher NTRK3 expression was correlated with worse progression‐free survival, cancer‐specific survival, and overall survival. Moreover, the results of an Ingenuity Pathway Analysis suggested that NTRK3 may interact with the PI3K‐AKT‐mTOR signaling pathway to promote cancer. NTRK3 downregulation in BFTC909 cells through shRNA reduced cellular migration, invasion, and activity in the AKT‐mTOR pathway. Furthermore, the overexpression of NTRK3 in UM‐UC‐14 cells promoted AKT‐mTOR pathway activity, cellular migration, and cell invasion. From these observations, we concluded that NTRK3 may contribute to aggressive behaviors in UTUC by facilitating cell migration and invasion through its interaction with the AKT‐mTOR pathway and the expression of NTRK3 is a potential predictor of clinical outcomes in cases of UTUC.